Facial bradykinesia. Issue 6 (12th December 2012) - Bologna, Matteo; Fabbrini, Giovanni; Marsili, Luca; Defazio, Giovanni; Thompson, Philip D; Berardelli, Alfredo
Abstract : The aim of this paper is to summarise the main clinical and pathophysiological features of facial bradykinesia in Parkinson's disease (PD) and in atypical parkinsonism. Clinical observation suggests that reduced spontaneous and emotional facial expressions are features of facial bradykinesia in PD and atypical parkinsonism. In atypical parkinsonism, facial bradykinesia is complicated by additional dystonic features. Experimental studies evaluating spontaneous and emotional facial movements demonstrate that PD is characterised by a reduction in spontaneous blinking and emotional facial expression. In PD, neurophysiological studies show that voluntary orofacial movements are smaller in amplitude and slower in velocity. In contrast, movements of the upper face (eg, voluntary blinking) are normal in terms of velocity and amplitude but impaired in terms of switching between the closing and opening phases. In progressive supranuclear palsy (PSP), voluntary blinking is not only characterised by a severely impaired switching between the closing and opening phases of voluntary blinking, but is also slow in comparison with PD. In conclusion, in PD, facial bradykinesia reflects abnormalities of spontaneous, emotional and voluntary facial movements. In PSP, spontaneous and voluntary facial movements are abnormal but experimental studies on emotional facial movements are lacking. Data on facial bradykinesia in other atypical parkinsonism diseases, including multiple system atrophy and corticobasal degeneration, are limited. In PD, facial bradykinesia is primarily mediated by basal ganglia dysfunction whereas in PSP, facial bradykinesia is a consequence of a widespread degeneration involving the basal ganglia, cortical and brainstem structures.